RETRACTED: Gupta et al. Self-Gelling Solid Lipid Nanoparticle Hydrogel Containing Simvastatin as Suitable Wound Dressing: An Investigative Study. Gels 2022, 8, 58 - Bhumika Gupta; Garima Sharma; Pratibha Sharma; Simarjot Kaur Sandhu; Indu Pal Kaur (Gels)
The journal retracts the article titled “Self-Gelling Solid Lipid Nanoparticle Hydrogel Containing Simvastatin as Suitable Wound Dressing: An Investigative Study” [...]